ANALISIS PENGARUH KUALITAS JASA PELAYANAN TERHADAP KEPUASAN MAHASISWA - Agatha Septianna; ANTONNY WIJAYA WIJAYA; PRISCA YENIYATI YENIYATI (Catholic University Musi Charitas, 2019)
The aim of this reseach is to analyze the impact of Service Quality towards Students’ Satisfaction within Musi Charitas Chatolic University (MCCU). Service quality has five determinant factors that are reliability, responsiveness, assurance, emphathy and tangible. These determinants must fit with MCCU basic values CHAMPION. Research sample of 214 students from three faculties of MCCU used convenience sampling technique. Data analyze technique used Simple Regression and frequent tabulation. The results showed that students have not been satisfied yet with the service quality required and student still need continuously improvement to improve sustainability competitiveness.